2013
DOI: 10.1371/journal.pone.0063271
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Hospital-Based Work Support Intervention for Female Cancer Patients – A Multi-Centre Randomised Controlled Trial

Abstract: ObjectiveOne key aspect of cancer survivorship is return-to-work. Unfortunately, many cancer survivors face problems upon their return-to-work. For that reason, we developed a hospital-based work support intervention aimed at enhancing return-to-work. We studied effectiveness of the intervention compared to usual care for female cancer patients in a multi-centre randomised controlled trial.MethodsBreast and gynaecological cancer patients who were treated with curative intent and had paid work were randomised t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 35 publications
0
91
0
Order By: Relevance
“…also stress on the need for an early start to enhance results of RTW interventions, without being more precise on the timing or an exact moment in the treatment process: ‘ An early intervention – meaning soon after diagnosis or early in treatment – is most appropriate because the longer the duration of sick leave, the more difficult return‐to‐work is to achieve ’ (Tamminga et al . ). This also aligns with findings of Peterson et al ., who conclude that shortly after BC surgery, most women valued work highly, even as one of the most important things in their lives.…”
Section: Discussionmentioning
confidence: 97%
“…also stress on the need for an early start to enhance results of RTW interventions, without being more precise on the timing or an exact moment in the treatment process: ‘ An early intervention – meaning soon after diagnosis or early in treatment – is most appropriate because the longer the duration of sick leave, the more difficult return‐to‐work is to achieve ’ (Tamminga et al . ). This also aligns with findings of Peterson et al ., who conclude that shortly after BC surgery, most women valued work highly, even as one of the most important things in their lives.…”
Section: Discussionmentioning
confidence: 97%
“…In other RTW studies for CSs, although not specifically for CSs with job loss, the findings on health-related outcomes are, at best, ambiguous. That is, the study by Tamminga et al (2013) found no significant effect of their RTW program on quality of life [22]. However, the study by Van Waart et al (2015) showed improvements in physical functioning and reduction of symptoms, such as fatigue [21].…”
Section: Interpretation Of Findingsmentioning
confidence: 96%
“…In contrast, in other studies no effect of interventions programs on RTW was found. For instance, a recent study by Tamminga et al (2013), which offered a hospital-based vocational intervention program to CSs, demonstrated no effect of the intervention program on RTW compared to usual care [22]. It should be mentioned that previous studies were not aimed at CSs with job loss.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…In a similar way, another study evaluated a case management intervention that tailored individual plans to integrate both physical and counseling components (Hubbard et al, 2013). Only two interventions directly addressed return-to-work or job-related issues by establishing return-to-work plans for cancer survivors combined with informational sessions (Tamminga et al, 2013) or therapy on job-related issues with physical therapy (Bottcher et al, 2013) (see Figure 2 for a checklist of intervention components across studies).…”
Section: Interventionsmentioning
confidence: 99%
“…Risk of detection bias was low for three studies that specified that assessors were blinded to participants' allocation (Hubbard et Attrition bias. Attrition was generally well reported (low risk of bias) in the included studies, which often explained attrition due to one or a combination of the following: cancer recurrence, misdiagnosis, decline, refusal to participate, or death (Berglund et al, 1994;Gordon et al, 1980;Hubbard et al, 2013;Lepore et al, 2003;Maguire et al, 1983;Tamminga et al, 2013). Some studies acknowledged the presence of attrition in their studies but did not discuss reasons (Bottcher et al, 2013;Capone et al, 1980;Granstam-Bjorneklett et al, 2013).…”
Section: Risk Of Biasmentioning
confidence: 99%